A novel loss of function mutation in the HAVCR2 gene in a patient diagnosed with Hodgkin’s lymphoma - Serife Erdem; Ebru Yilmaz; Alper Ozcan; Ahmed Nazim Canatan; Atil Bisgin; Muhammet Ensar Dogan; Musa Karakukcu; Ekrem Unal; Ahmet Eken (Immunologic Research, 2025)

BMAP-27 Peptide Reduces Proliferation and Increases Apoptosis in Primary and Metastatic Colon Cancer Cell Lines - Alakesh Das; Dikshita Deka; Nabajyoti Baildya; Antara Banerjee; Atil Bisgin; Suman Adhikari; Asim K. Duttaroy; Surajit Pathak (International Journal of Peptide Research and Therapeutics, 2023)
BMAP-27 peptide is reported to possess apoptotic and anti-proliferative effects against cancer cells but the actual mechanism of action is yet to be investigated. In the current investigation, we aimed to study the role of the BMAP-27 peptide in reducing proliferation and increasing apoptosis in colon cancer cell lines. In this study, we used primary and metastatic colon cancer cell lines SW480 and SW620. Cell proliferation was measured using MTT and CCK-8 assays, and cellular damage was analyzed by lactate dehydrogenase assay. Apoptosis, cell cycle, and proliferation potentials were measured by the expression of CASPASE3, BAX, BCL-2, TP53, CDK-6, PCNA, WNT11, AXIN1 , and CTNNB1 genes. Additionally, in-silico studies were conducted to determine the binding affinities of BMAP-27 with adenomatous polyposis coli (APC) and β-catenin proteins, one of the primary regulators of colon cancer. BMAP-27 peptide reduced colon cancer cell proliferation, upregulated tumor suppressor genes CASPASE3, BAX, TP53, AXIN1 expression, and downregulated the expression of oncogenes BCL-2, CDK-6, PCNA, WNT11, CTNNB1 in both the cell lines, however, in the primary colon cancer cell line the changes are found to be more significant. The molecular dynamic simulation analysis revealed substantial binding affinity of the peptide to APC and β-catenin proteins. BMAP-27 peptide significantly inhibited the proliferation and induced apoptosis in the primary colon cancer cell line than in the metastatic colon cancer cell line. In-silico results suggest that BMAP-27 shows a strong binding affinity with APC and β-catenin proteins, highlighting its role in inhibiting colon cancer cell proliferation.

An Updated Review on Recent Advances in the Usage of Novel Therapeutic Peptides for Breast Cancer Treatment - Alakesh Das; Suman Adhikari; Dikshita Deka; Atil Bisgin; Sujay Paul; Nabajyoti Balidya; Ibrahim Boga; Antara Banerjee; Surajit Pathak (International Journal of Peptide Research and Therapeutics, 2023)

Clinical and molecular evaluation of MEFV gene variants in the Turkish population: a study by the National Genetics Consortium - Munis Dundar; Umut Fahrioglu; Saliha Handan Yildiz; Burcu Bakir-Gungor; Sehime Gulsun Temel; Haluk Akin; Sevilhan Artan; Tulin Cora; Feride Iffet Sahin; Ahmet Dursun; Ozlem Sezer; Hakan Gurkan; et al. (Functional & Integrative Genomics, 2022)

MEDNIK syndrome with a frame shift causing mutation in AP1S1 gene and literature review of the clinical features - Faruk Incecik; Atil Bisgin; Mustafa Yılmaz (Metabolic Brain Disease, 2018)